Inovasi Digital dalam Murajaah Al-Qur’an: Potensi dan Relevansi Aplikasi Al-Qur’an Indonesia - Nurfadilah, Nurfadilah (Journal of Society and Development, 2023)
As Muslims, the problem of memorizing the Al-Qur’an is a desire and dream that needs to be fulfilled. Bonding with Allah and the Al-Qur’an is a special thing for every Muslim. The purpose of this study is to discuss the relevance of the application of the Al-Qur’an Indonesia in supporting the memorization of every Muslim. This research is a type of qualitative research through literature study and interviews by applying content analysis. The results and discussion of this research are that the Indonesian Al-Qur'an is quite recommended to help learn the Al-Qur’an and memorize murajaah. And it is important for users to have study friends who both understand the rules of reading the Al-Qur’an that are good and correct. The goal is to not only understand theory, but can be systematically practiced with study partners. The conclusion of this research is the Al-Qur’an Indonesia application is quite relevant in helping murajaah memorize, read the Al-Qur’an, and listen to murattal from a very competent qori. In addition to dealing with the Al-Qur’an, this application also has a prayer reminder feature in the form of an automatic call to prayer, a five daily prayer schedule, and a hijri calendar for prayer times. This study recommends emphasizing learning first in the aspect of study groups (maybe via online) as a form of monitoring memorizing or reading the Al-Qur’an.